ANALYSIS OF REWARDING AND PUNISHMENT ON CV. PUTRA PERSADA MANDIRI SOUTH TANGERANG - Agrasadya, Agrasadya; Sunarto, Ading (Yayasan Education and Social Center, 2023)
This study aims to determine how the strategies, forms, and challenges of giving rewards and punishments to CV. Putra Persada Mandiri South Tangerang as the object of research. The method used in this research is descriptive and uses a qualitative approach. The instruments used are interviews (interviews), chain of evidence, focus group discussions (FGD) and SWOT analysis. Information obtained in this study, came from sources and informants, namely 1 (one) manager and 5 (five) employees of CV. Putra Persada Mandiri. The results of this study are a reward strategy given by employees when employees have good work performance through indicators that have been set by the company such as work discipline, enthusiasm for work, and compliance with applicable regulations. Punishment is given in the form of light punishment, moderate punishment, and severe punishment to every employee who violates the applicable rules. The most effective form of reward on CV. Putra Persada Mandiri, namely in the form of money (financial) and the form of punishment given by the company in the form of verbal warnings that pay attention to the psychological condition of employees. Challenges faced by CV. Putra Persada Mandiri in providing rewards, namely in the form of increasing the provision of rewards in the form of money (financial) in accordance with employee expectations. Meanwhile, the challenge in giving punishment is the provision of stricter sanctions/punishments but educating and leading to improvement